Implementasi Jual Beli Pesanan (Istishna’) Pada Usaha Lemari Kaca Pada Kecamatan Banda Alam Kabupaten Timu rAceh - fuadi fuadi; Munardi Munardi; Rani Puspita Ningrum; Muhammad Ikbal (Faculty of Economics and Business, Universitas Malikussaleh, 2023)
This study aims to determine whether the buying and selling system carried out is in accordance with Islamic law and the application of the istishna contract on buying and selling orders in the glass Haikal glass business of Banda Alam district. Istishna is defined as a contract asking a person to make a certain item in a certain form. This research methodology uses qualitative research methods with a descriptive analysis approach, based on financial reports and the results of interviews between producers and consumers. The results of this study The buying and selling process carried out by the glass cabinet business Haikal glass is in accordance with the terms and pillars of buying and selling in Islam, where the perpetrators of buying and selling voluntarily there is no element of coercion and mutual pleasure. The buying and selling process carried out by Haikal kaca has unwittingly applied the pillars and conditions of buying and selling istishna, where Haikal kaca has implemented buying and selling, that is, with the buyer ordering directly to ask for a product and ask for dp as a milestone. The application of buying and selling istishna in the glass business has not been fully perfected, because there are still delays in the completion of goods that exceed the time in the agreement and there are goods that do not match the specifications desired by the buyer.